Breve aproximación a la protección ambiental desde los objetivos del milenio en América Latina y el Caribe (2009)
After eight years of the Millennium Summit, one wonders about the fulfillment of the seventh goal concerning the environment. In this short essay the Latin America case will be analyzed based on data provided by some international organizations, which reflect the lack of progress in the achievement of the target.